Síntese e caracterização de hidróxidos duplos lamelares para adsorção de o-nitrofenol de soluções aquosas - Marques, Bianca Silva (2020)
In this work, layered double hydroxides (LDHs) based on calcium-aluminium (Ca-Al), nickel-aluminium (Ni-Al) and zinco-aluminium (Zn-Al) were evaluated at adsorptive removal of o-nitrophenol from aqueous solutions. The materials LDHs were obtained by the co-precipitation synthetic route; and after submitted to characterization techniques, such as SEM, FT-IR, XRD, EDS, BET and pHPZC. At adsorption studies, the effects of pH, kinetics, equilibrium, simulated effluent and regeneration were analysed. For kinetics step, models of pseudo-first order, pseudo-second order, general order and Avrami were fitted to experimental data; while Freundlich, Langmuir, Redlich-Peterson, Sips and Toth models were employed for equilibrium data. From characterization techniques, it was verified the formation of typical layered double hydroxide structure for the three synthetized materials. At the pH study, maximum removal percentages were obtained between 70 and 90% at pH 5. Kinetic experimental data obeyed the general order model for the three LDHs. In the step inherent to equilibrium, the experimental data had its behavior best represented by the Sips model. Also, maximum adsorption capacities obtained were equal to 35 mg g -¹, 122 mg g-¹ and 130mg g-¹ for Ca-Al, Ni-Al and Zn-Al layered double hydroxides, respectively. At simulated effluent study, the removal up to 60% for the LDH based on Ni-Al. At the regeneration of materials, it was verified a preservation of original adsorption capacity up to four cycles for the layered double hydroxide of Ni-Al, while Ca-Al and Zn-Al exhibited a significant reduction in its adsorption capacities still in the second regeneration cycle. Therefore, the three layered double hydroxides demonstrated potential as adsorbents of o-nitrophenol in aqueous solutions; and the material of Ni-Al showed better performance in relation to simulated effluent and regeneration studies.